Seizures after intracranial surgery in pediatric patients - Anannit Visudthibhan (2018)
We retrospectively reviewed the occurrence of seizure after performing intracranial operations in children aged less than 15 years. During a 5-year period, there were 18 patients out of a total of 155 who developed one or more seizures within 1 year after operation. The majority of patients (55.6%) had the onset of seizures within 24 hours. Seventy-two per cent of the patients had partial seizures. Two patients who developed immediate postoperative seizures had sodium derangement. Eight of 10 patients who had early onset seizures had had an operation for supratentorial lesions. Among the 6 patients who developed seizures after infratentorial tumor removal, the cause of seizure was not known in 4 patients. We emphasize that prompt investigations to exclude any structural lesions and other possible causes of seizure, especially electrolyte disturbance along with appropriate antiepileptic drug administration, are important in patients who develop seizures after the operation. The recommendation for routine administration of antiepileptic drug prior to the operation has yet to be concluded.